Application of the Internet of Things (IoT) in Pest and Plant Disease Control: A Systematic Review and Analysis of Technology Trends - Raodatul Putri (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Pests and plant diseases pose a serious threat to global agricultural productivity that can cause crop losses of up to 40%. Internet of Things (IoT) technology is emerging as an innovative solution to improve the effectiveness of pest and disease control through real-time monitoring, early detection, and timely intervention. This study aims to analyze the implementation of IoT technology in pest and plant disease control through a systematic review approach of 12 scientific journals for the 2020-2025 period. The method used is a systematic literature review with the PRISMA protocol to identify, evaluate, and synthesize related research findings. The results of the analysis show that the integration of IoT with supporting technologies such as UAVs, computer vision, and blockchain creates a comprehensive pest control ecosystem. IoT sensors are capable of monitoring microclimate parameters (temperature 14-16°C increases the risk of powdery mildew), while thermal cameras achieve 92% detection accuracy. IoT systems have also been successfully applied to various commodities (rice, tomatoes, cucumbers) with a combination of ozone and light traps to minimize the use of chemical pesticides. Key implementation challenges include energy consumption, data security, system interoperability, and initial investment costs. The study concludes that IoT technology has great potential to transform pest control practices towards more efficient and environmentally friendly sustainable agriculture.